2006
DOI: 10.1063/1.2402905
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of B clustering in amorphous Si during ultrashallow junction formation

Abstract: The authors have investigated ultrashallow p(+)/n-junction formation by solid-phase epitaxy, by using x-ray absorption near-edge spectroscopy measurements on the B K edge. A clear fingerprint of B-B clusters is detected in the spectra. The authors demonstrate that B clustering occurs during the very early stages of annealing-induced Si recrystallization, i.e., when B is still in an amorphous matrix. After complete regrowth the local structure around B remains the same as in the amorphous phase, implying that B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
5
13
0
Order By: Relevance
“…16 Moreover, sheet resistance measurements after low temperature recrystallization are also consistent with maximum levels of B activation of around $2 Â 10 20 B/cm 3 . 7,8 All these observations support the hypothesis of formation of immobile BICs in amorphous Si at B concentrations higher than that limit value, as experimentally verified by De Salvador et al 17 By using theoretical calculations, Mattoni and Colombo have characterized the formation kinetics of some BICs during recrystallization and found that B 2 I, B 3 I and B 4 I 2 configurations could play the major role in the evolution of recrystallized B-doped Si. 18 However, there are still some uncertainties about the configurations of BICs after recrystallization and the kinetics of their nucleation in amorphous Si is generally not modeled in detail.…”
Section: Introductionsupporting
confidence: 76%
“…16 Moreover, sheet resistance measurements after low temperature recrystallization are also consistent with maximum levels of B activation of around $2 Â 10 20 B/cm 3 . 7,8 All these observations support the hypothesis of formation of immobile BICs in amorphous Si at B concentrations higher than that limit value, as experimentally verified by De Salvador et al 17 By using theoretical calculations, Mattoni and Colombo have characterized the formation kinetics of some BICs during recrystallization and found that B 2 I, B 3 I and B 4 I 2 configurations could play the major role in the evolution of recrystallized B-doped Si. 18 However, there are still some uncertainties about the configurations of BICs after recrystallization and the kinetics of their nucleation in amorphous Si is generally not modeled in detail.…”
Section: Introductionsupporting
confidence: 76%
“…II), even if to a lower extent than in crystalline Si, and then these clusters are transferred to the crystalline structure during the SPER. 6,12,13 Such B clusters, even if formed in preamorphized Si, can evolve towards BICs as large as 8 nm if a high B concentration is present and subjected to a proper I supersaturation, as shown by B chemical mapping and energyfiltered TEM investigations. 96 In summary, the non equilibrium clustering of B induced by a supersaturation of Is gives out B:Si complexes, named BICs, whose size and thermal stability depend on the starting conditions.…”
Section: B-i Clusters Formation and Dissolutionmentioning
confidence: 99%
“…Actually, the formation of B-B pairs during the very early stages of annealing at 550 C, while B is still in the amorphous phase of Si, has been evidenced by x-ray absorption near-edge spectroscopy measurements of p þ /n ultrashallow junctions realized by solid-phase epitaxy. 13 The clustered B, formed in a-Si, is then transferred to the c-Si once the SPER is complete, being responsible for the B deactivation measured in the final device.…”
Section: B Main Features Of B Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…After amorphization, the channel dopants experience diffusion in the a-Si layer. For the B diffusion in the a-Si during the SPER annealing stage, enhanced B diffusion [2] and B clustering phenomenon [18] are also considered. The LA process based on multiple laser stripe overlays leads to microscopic variations of Rs [19] and transistor properties [6].…”
Section: Pocket Dopant Deactivation Analysismentioning
confidence: 99%